The effects of urbanization on felid populations, interactions, and pathogen dynamics - Lewis, Jesse Scherer, author; Crooks, Kevin, advisor; VandeWoude, Sue, committee member; Bailey, Larissa, committee member; Theobald, David, committee member; Alldredge, Mat, committee member (Colorado State University. Libraries, 2014)
Urbanization is one of the most ecologically impactful forms of landscape conversion with far-reaching effects on landscape pattern and process, particularly related to animal populations. We evaluated how urbanization affected population density, interspecific interactions, and pathogen exposure in wild felid populations. Specifically, we studied bobcats and pumas across wildland, exurban development, and wildland-urban interface (WUI) habitat to test hypotheses evaluating how urbanization impacts wild felids. Low-density residential development appeared to have a greater impact on felid population density compared to habitat adjacent to a major urban area; point estimates of population density were lower for bobcats and pumas in exurban development compared to wildland habitat, whereas population density for both felids appeared more similar between WUI and wildland habitat. For competitive interactions, occupancy modeling indicated that bobcats did not avoid pumas across broad spatial and temporal scales; however, at finer scales bobcats temporally avoided pumas in wildland areas, but did not appear to avoid pumas in urbanized habitat. Using telemetry data, contact networks revealed that space-use extent was an important predictor of possible social interactions, but that felids associated with urbanization did not appear to exhibit increased potential for interspecific interactions. Lastly, we provided a conceptual framework for evaluating the effects of multiple ecological mechanisms on patterns of pathogen exposure in animal populations; we demonstrated how demographic, social, and environmental characteristics affected the pathogen exposure in bobcat and puma populations across a gradient of urbanization.